Analisis Solvabilitas Anggaran Kabupaten/Kota di Provinsi Sumatera Selatan Tahun Anggaran 2016-2022 - Irfandhia Nugraha, Muhammad; Masnila, Nelly; Indriasari, Desi (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The purpose of this study was to determine the solvency of the budget at the Regency and City Governments in the Province of South Sumatra. This study uses a quantitative method with a descriptive approach. Secondary data in the form of Financial Statements to be analyzed is the Budget Realization Report for Regencies and Cities in South Sumatra Province for the 2016-2020 Fiscal Year. The budget solvency analysis uses the calculation of the budget solvency ratio, the budget solvency ratio index, and the budget solvency dimension index which are the final results to determine the budget solvency value. Based on the results of the analysis, it is known that the budget solvency in the districts and cities in South Sumatra Province shows quite good results, where within 5 years all districts and cities in South Sumatra Province have passed the indicator of the local government financial health value for budget solvency by showing an average increasing every year, although in 2020 it decreased again due to the covid-19 pandemic.